REVIEW OF THE USE OF BACTERIA AS A HEALING AGENT IN HIGH STRENGTH CONCRETE - Putra Ardhani, Rifki Rezkya; Oksri Nelfia, Lisa; Amiri, Ouali (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2025)
The need for high quality concrete continues to increase along with infrastructure growth in Indonesia. However, high quality concrete is more brittle and susceptible to cracking. One innovative solution to overcome this problem is the application of self-healing concrete technology by utilizing bacteria as healing agents. This research is a literature review that discusses the use of bacteria such as Bacillus megaterium, Staphylococcus sp., and Solibacillus as self-healing agents in high quality concrete. This bacteria is able to produce the urease enzyme which triggers the formation of calcium carbonate (CaCO₃), which then fills micro cracks in concrete, thereby increasing the density and compressive strength of the concrete. Based on the studies reviewed, the addition of encapsulated bacteria, either as a partial replacement for coarse aggregate or mixed with water, can increase compressive strength by more than 12% compared to control concrete. This research concludes that the use of bacteria as self-healing agents has great potential in increasing the durability and structural performance of high quality concrete in a sustainable manner.